AI AND AUTOMATION IN THE DIGITAL ERA: A LITERATURE REVIEW OF TECHNOLOGY DEVELOPMENT AND REGULATION - Loso Judijanto; Edwin Aldrin W. Sanadi (Adisam Publisher, 2024)
This article reviews the literature on the development of artificial intelligence (AI) and automation technologies, and the accompanying regulatory efforts in the digital era. AI and automation have progressed rapidly, bringing benefits such as higher operational efficiency, cost reduction, and innovation in various sectors. However, these developments also bring significant challenges including privacy issues, algorithm bias, and labour impacts. Regulation plays a key role in guiding these technological developments, with the aim of protecting personal data, increasing transparency and accountability, and preventing discrimination. This article highlights the importance of creating responsive and proactive policies so that the benefits of AI and automation can be optimised, while the risks are minimised.